2015
DOI: 10.1016/j.icarus.2014.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of H2O, CO, and CO2 production in Comet C/2009 P1 Garradd during the 2011–2012 apparition

Abstract: We present analysis of high spectral resolution NIR spectra of CO and H 2 O in comet C/2009 P1 (Garradd) taken during its 2011-2012 apparition with the CSHELL instrument on NASA's Infrared Telescope Facility (IRTF). We also present analysis of observations of atomic oxygen in comet Garradd obtained with the ARCES echelle spectrometer mounted on the ARC 3.5-meter telescope at Apache Point Observatory and the Tull Coude spectrograph on the Harlan J. Smith 2.7-meter telescope at McDonald Observatory. The observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…Decock et al (2013) reported a mean value of 0.11 for their sample of 11 comets, which is about twice lower than what we measure for R2. However, both Decock et al (2013) and McKay et al (2015) reported that comets observed at larger heliocentric distance have higher values of the G/R ratio. For example, Decock et al (2013) The G/R ratio measured for R2 is thus consistent with the ratio measured for other comets observed at large heliocentric distances.…”
Section: [Ni] [Oi] and [Ci] Forbidden Atomic Linesmentioning
confidence: 97%
“…Decock et al (2013) reported a mean value of 0.11 for their sample of 11 comets, which is about twice lower than what we measure for R2. However, both Decock et al (2013) and McKay et al (2015) reported that comets observed at larger heliocentric distance have higher values of the G/R ratio. For example, Decock et al (2013) The G/R ratio measured for R2 is thus consistent with the ratio measured for other comets observed at large heliocentric distances.…”
Section: [Ni] [Oi] and [Ci] Forbidden Atomic Linesmentioning
confidence: 97%
“…Line ratios of [O i] may be used to determine the column density ratios of H 2 O, CO 2 , and CO (Delsemme 1980;Festou & Feldman 1981;Bhardwaj & Raghuram 2012). However, the release rates of [O i] in the relevant states as well as physical processes in the coma that may affect these lines are not yet completely understood, resulting in large uncertainties in the derived abundances (McKay et al 2012;DeCock et al 2013 and references therein).…”
Section: Did Co 2 Drive the Icy Grains?mentioning
confidence: 99%
“…Based on [O i] observations at Apache Point Observatory, McKay et al (2012) suggest constant CO 2 abundances of order 10%-15% within 2 AU pre-and post-perihelion. Finally, the Deep Impact spacecraft measured a CO 2 /H 2 O abundance of 8% at 2 AU post-perihelion (Feaga et al 2014).…”
Section: Did Co 2 Drive the Icy Grains?mentioning
confidence: 99%
“…Comet researchers usually have to resort to remote observations. Numerous studies have been devoted to the direct observation of atomic oxygen lines [Morgenthaler et al, 2007;Cochran, 2008;McKay et al, 2015]. Photodissociation of H 2 O, CO 2 , and CO results in the release of an oxygen atom in an excited state, either O( 1 D) or O( 1 S).…”
Section: Introductionmentioning
confidence: 99%